PENGARUH KEPERCAYAAN MUZAKKI KEPADA INSTITUSI ZAKAT DALAM MENUNAIKAN ZAKATNYA DI BAITUL MAL KABUPATEN PIDIE - Rahmad, Rahmad (Jurnal Tahqiqa : Jurnal Pemikiran Hukum Islam, 2023)
Zakat apart from being a mahdhah worship service, also functions as a social service that can be used as an instrument for eradicating the poverty of today's people in Aceh. The potential for zakat in Aceh is so great that it cannot be optimized if the zakat institution has not won the heart of the muzakki who are the holders of the zakat mandate itself. Baitul Mal's income from the zakat sector is highly dependent on the muzakki's trust in zakat managers in these official institutions. The percentage and frequency are also very high so that the influence of the muzakki's trust in amil institutions greatly determines his desire to choose Baitul Mal as a place to pay his zakat.